การสร้างสรรค์นาฏยศิลป์จากเรื่องราวของความทุกข์ที่เสมือนนรกในใจคน - สุเมธ ป้อมป้องภัย (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
In this thesis, the researcher studied the creation of dance from misery identified as inferno of mind. The objective of this piece is to find the style and concept obtained after the creation. The researcher uses both qualitative research and creative research. and research that studied information from documents relating to research topics, interviews, information medias, observations, standardization criteria of artists and the researcher s personal experiences to be guideline for analyzing, synthesizing and creating dancing works.The study shows that there are 8 elements in this creative Thai dance, which are 1) A five acts script inspired from the researcher’s direct experience, including Act 1 Loneliness, Act 2 Incomplete Elements, Act 3 Imagining Things, Act 4 Restlessness, and Act 5 Inferno of Mind. 2) Two actors who are different in their Thai dance and Performing skills. 3) Dance movements from everyday movement, implemented as the basic dance movements. Then, the researcher has designed the dance moves from the western and eastern traditional dance, comprised of Thai classical dance, Ballet, and Bharatanatyam. 4) The sound and music accompanying the performance from electronic instruments and synthesizers. 5) Stage props such as canvas and easel. 6) Graphic pattern costumes 7) Coloration of lighting creates the mental state dimensions of place and time. 8) Stage area of the Black Box Theatre. Additionally, the researcher has summarized the five concepts obtained from the dance creation inspired by an Inferno of Mind, consisted of 1) The stories of grief that represents an Inferno of Mind 2) Communication with the new generation audience 3) Theory and concept of dance and visual arts 4) Symbolism in the dance creation 5) Creativity in the dance creation. The study result of the dance performance elements reflected through the creation of dance performance from the story of grief that resembles an Inferno of Mind, which satisfied all the objectives set beforehand.